Shoulder impingement syndrome in relation to shoulder intensive work. Issue 7 (1st July 1999) - Frost, P; Andersen, J H
Abstract : OBJECTIVES: To analyse the risk of shoulder impingement syndrome relative to shoulder intensive work. METHODS: A cross sectional study of a historical cohort of 1591 workers employed between 1986 and 1993 at a slaughterhouse or a chemical factory. Workers not doing tasks in slaughtering or meat processing constituted the reference group. Intensity of shoulder work in meat processing tasks was assessed by video based observations. Information on shoulder disorders was collected by questionnaire and by physical examinations. Impingement syndrome was diagnosed when shoulder symptoms had been present for at least 3 months during the past year and there were signs of subacromial impingement in the corresponding shoulder at physical examination. Shoulder function was assessed at the same occasion with the Constant scoring technique. Prevalence of shoulder impingement syndrome was analysed according to job title and cumulative exposure. RESULTS: Prevalence ratio for shoulder impingement syndrome was 5.27 (95% confidence interval (95% CI), 2.09 to 12.26) among currently working and 7.90 (95% CI, 2.94 to 21.18) among former slaughterhouse workers. Transformed model based prevalence ratios according to years in slaughterhouse work showed an overall association between cumulative exposure and risk for shoulder impingement syndrome. CONCLUSIONS: This study supports the hypothesis that shoulder intensive work is a risk factor for impingement syndrome of the shoulder. Despite the historical cohort design healthy worker selection may have influenced the exposure-response relation found.